History and Memory of a Venezuelan in Cienfuegos: Tomás Terry Adams (1830-1882) (Islas, 2025)
Introduction: The aim of this study is to explain the strategies and mechanisms employed by Tomás Terry Adams as an expression of modern instrumental rational thought in Cienfuegos between 1830 and 1882, as well as his legacy to the city.Methods: The logical-historical method was used to interpret the sources that reveal the subject’s actions, based on contact with reality and assimilation of context; the analytical–synthetic and inductive–deductive methods were applied in processing information to interrelate content.Results: It highlights the origins and family background of a Venezuelan who established himself in Cienfuegos between 1830 and 1882, joining the elite; engaging in commerce and trade; economic associations and coastal maritime transport; the sugar business; and making investments inside and outside Cuba through networks, refurbishment, and capitalization. He also bequeathed a tangible cultural heritage to the city.Conclusions: Tomás Terry Adams used strategies and mechanisms grounded in modern instrumental rationality to build, launch, develop, and consolidate a fortune in Cienfuegos between 1830 and 1882. The tangible cultural heritage he left behind forms part of the city’s cultural patrimony.
Keywords: 19th-century Cuban; Tomás Terry; modern instrumental rationality; tangible cultural heritage; history of Cienfuegos; history of Cuba